Exploration of the skeletal phenotype of the Col1a1+/Mov13 mouse model for haploinsufficient osteogenesis imperfecta type 1 - Claeys, Lauria; Zhytnik, Lidiia; Wisse, Lisanne E.; van Essen, Huib W.; Eekhoff, E. Marelise W.; Pals, Gerard; Bravenboer, Nathalie; Micha, Dimitra (Frontiers in Endocrinology, 2023)
Osteogenesis Imperfecta is a rare genetic connective tissue disorder, characterized by skeletal dysplasia and fragile bones. Currently only two mouse models have been reported for haploinsufficient (HI) mild Osteogenesis Imperfecta (OI); the Col1a1+/Mov13 (Mov13) and the Col1a1+/-365 mouse model. The Mov13 mice were created by random insertion of the Mouse Moloney leukemia virus in the first intron of the Col1a1 gene, preventing the initiation of transcription. Since the development of the Mov13 mice almost four decades ago and its basic phenotypic characterization in the 90s, there have not been many further studies. We aimed to extensively characterize the Mov13 mouse model in order to critically evaluate its possible use for preclinical studies of HI OI. Bone tissue from ten heterozygous Mov13 and ten wild-type littermates (WT) C57BL/6J mice (50% males per group) was analyzed at eight12 weeks of age with bone histomorphometry, micro computed tomography (microCT), 3-point bending, gene expression of different collagens, as well as serum markers of bone turnover. The Mov13 mouse presented a lower bone strength and impaired material properties based on our results of 3-point bending and microCT analysis respectively. In contrast, no significant differences were found for all histomorphometric parameters. In addition, no significant differences in Col1a1 bone expression were present, but there was a significant lower P1NP concentration, a bone formation marker, measured in serum. Furthermore, bone tissue of Mov13 mice presented significantly higher expression of collagens (Col1a2, Col5a1 and Col5a2), and bone metabolism markers (Bglap, Fgf23, Smad7, Edn1 and Eln) compared to WT. Finally, we measured a significantly lower Col1a1 expression in heart and skin tissue and also determined a higher expression of other collagens in the heart tissue. Although we did not detect a significant reduction in Col1a1 expression in the bone tissue, a change in bone structure and reduction in bone strength was noted. Regrettably, the variability of the bone phenotype and the appearance of severe lymphoma in adult Mov13 mice, does not favor their use for the testing of new long-term drug studies. As such, a new HI OI type 1 mouse model is urgently needed.